KAJIAN KRITIS TERHADAP UNDANG-UNDANG REPUBLIK INDONESIA NOMOR 14 TAHUN 2005 TENTANG GURU DAN DOSEN - Sidiq, Umar (Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2015)
If the teacher has been able to master the material to be taught, the teacher must be able to actualize themselves. Continuous training is the answer. Both the methodology of teaching and understanding the philosophy and the accompanying paradigm. This training should be coupled with endeavors to develop the sensitivity and creativity of each teacher, to develop their own methodologies appropriate for each student. Therefore, the Ministry of Religious Affairs (Kemenag) and the Ministry of Education (Kemendiknas) which is responsible for developing the professionalism and quality of teachers in Indonesia.